48. HEALTH STATUS OF WORKERS AT HA LONG SHIPBUILDING COMPANY, QUANG NINH PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the health status of workers at Ha Long Shipbuilding Company, Quang Ninh province in 2025.Methods: A cross-sectional study was conducted on 500 workers at Ha Long Shipbuilding Company, from January to March 2025. Data was collected through interviews, combined with retrospective review of the 2024 periodic health check-up results.Results: The proportion of workers with good and very good health was 66.2%, average was 32.6%, and poor health and very poor health accounted for only 1.2%. The most common diseases among workers included: ear nose throat (44.8%), eye (44%), musculoskeletal (41.6%), dental (24.8%), respiratory (20%). The occupational disease rate among workers was 22.8%. The rate of workers experiencing injuries in the past 12 months was 13.2%.Recommendations: It is necessary to strengthen the control of the working environment, provide protective equipment, and implement measures to reduce noise and dust.
Keywords: Health; workers; shipbuilding; Ha Long